2020
DOI: 10.1002/vnl.21767
|View full text |Cite
|
Sign up to set email alerts
|

Different Organic Peroxides that Cure Low‐k 1,2‐PB/SBS/EPDM Composites for High‐Frequency Substrate

Abstract: Since the advent of 5G network, polymeric low dielectric constant (low‐k) materials have been indispensable for high speed and stable signal transmission at microwave frequency. Herein, the low‐k composites of 1,2‐polybutadiene/styrene‐butadiene‐styrene triblock copolymer/ethylene‐propylene‐dicyclopentadiene (1,2‐PB/SBS/EPDM) were prepared with cured organic peroxide. Two structurally different organic peroxides, namely dicumyl peroxide (DCP) and bis(1‐(tert‐butylperoxy)‐1‐methylethyl)‐benzene (BIPB), were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…The introduction of highly crosslinked polymers in CCL can not only improve its thermal stability and dimensional stability but also effectively reduce its dielectric constant. For example, 1,2-polybutadiene (1,2 PB), styrene butadiene styrene triblock copolymer (SBS), and ethylene propylene dicyclopentadiene are ideal polymer matrices for CCL because they have good thermal stability through the formation of cross-linked structures. Benzocyclobutylene (BCB) is an all-hydrocarbon low-dielectric material with a simple and symmetrical structure, low polarity, and a low possibility of polarization to form a dipole, which makes the cured BCB resin have good thermal stability and a low dielectric constant so it can be used in microelectronics, large-scale integrated circuits, and other fields .…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of highly crosslinked polymers in CCL can not only improve its thermal stability and dimensional stability but also effectively reduce its dielectric constant. For example, 1,2-polybutadiene (1,2 PB), styrene butadiene styrene triblock copolymer (SBS), and ethylene propylene dicyclopentadiene are ideal polymer matrices for CCL because they have good thermal stability through the formation of cross-linked structures. Benzocyclobutylene (BCB) is an all-hydrocarbon low-dielectric material with a simple and symmetrical structure, low polarity, and a low possibility of polarization to form a dipole, which makes the cured BCB resin have good thermal stability and a low dielectric constant so it can be used in microelectronics, large-scale integrated circuits, and other fields .…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, the ternary blend of 1,2-polybutadiene (1, 2-PB)/styrene-butadiene-styrene triblock copolymer(SBS)/ ethylene-propylene-diene terpolymer(EPDM) in the most typical 1, 2-polybutyl dichloride system is used as the matrix, Selects the TiO 2 and SiO 2 both on the market the most commonly used oxide ceramic as a filler, [15][16][17][18][19][20] the preparation of a series of ceramic-polyolefin resin composite membrane, and the effects of alternating multilayer structures and different composite methods on the composite properties were investigated, [21][22] focusing on the most important dielectric properties, thermal stability and mechanical properties as substrate materials, and this work can provide some insights for better optimization of the performance aspects of ceramicpolyolefin resin composites. the above-mentioned layers can be seen that SiO 2 particles are irregular lumps, and larger than TiO 2 particle size, so the gap between each other is larger, filled with more resin, resin and SiO 2 combined with a weaker degree of tightness; while TiO 2 is a sheet-like structure, filler connection is very regular, arranged in the same direction, forming a multilayer structure, the amount of resin filled between the layers but the connection is weaker.…”
Section: Introductionmentioning
confidence: 99%
“…Among these resins, PB is the ideal material for high-frequency CCL due to its low D k , low D f and low toxicity. For instance, the RO 4000 ® series based on PB polymer matrix from Rogers corporation exhibit good performance as high-frequency circuit boards [ 15 ]. Based on ternary composite materials (PB/styrene/butadiene/styrene triblock copolymer (SBS)/ethylene/propylene/dicyclopentadiene (EPDM)), Bo and Wu et al found that appropriate crosslinking agents can more effectively enhance the degree of the crosslinking reaction in the material, and the modification of SiO 2 microspheres can improve the interfacial compatibility of different phases [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the RO 4000 ® series based on PB polymer matrix from Rogers corporation exhibit good performance as high-frequency circuit boards [ 15 ]. Based on ternary composite materials (PB/styrene/butadiene/styrene triblock copolymer (SBS)/ethylene/propylene/dicyclopentadiene (EPDM)), Bo and Wu et al found that appropriate crosslinking agents can more effectively enhance the degree of the crosslinking reaction in the material, and the modification of SiO 2 microspheres can improve the interfacial compatibility of different phases [ 15 , 16 , 17 , 18 ]. Xuan and Zhang et al designed a sandwich-structure composite material [ 19 , 20 ], with an intermediate layer of polytetrafluoroethylene (PTFE) and outer layers consisting of PB films or malefic–anhydride polybutadiene–amino-terminated polyamide oligomers films, achieving an ultra-low D f (0.0012).…”
Section: Introductionmentioning
confidence: 99%